Natural medicines for treating liver fibrosis by modulating post-translational modifications - Niu, Qun; Mou, Yu; Wang, Kaixin; Dong, Haijian; Zeng, Zijian; Li, Hui (Frontiers in Pharmacology, 2025)
Hepatic fibrosis is a multifactorial process driven by hepatic stellate cell (HSCs) activation, participation of Kupffer cells and infiltrating immune cells, and profibrotic cytokine signaling (notably TGF-β), culminating in excessive extracellular matrix (ECM) and collagen deposition. Post-translational modifications (PTMs)—covalent changes added after protein synthesis—govern protein stability, localization, interactions, and activity. Common PTMs include phosphorylation, acetylation, ubiquitination, glycosylation, nitration, and methylation; collectively, they modulate fibrogenic pathways across disease stages. Despite available therapies, clinically effective and well-tolerated antifibrotic options remain limited. Natural products, with their structural diversity, relative safety, and broad accessibility, offer promising leads for antifibrotic drug discovery. This review delineates the central roles of PTMs in hepatic fibrosis, synthesizes how specific PTMs drive disease initiation and progression, and evaluates natural products that target PTM-regulated nodes of fibrogenesis. We also propose strategies to accelerate development of PTM-informed antifibrotic therapeutics.